GREEN ACCOUNTING, CSR, AND ENVIRONMENTAL AUDITING OVERSIGHT IN MANUFACTURING FIRMS - Retnaningtyas Widuri; Chaterina Patricia; Jesslyn Nathania (Widya Mandala Surabaya Catholic University, 2026)
Research Purposes. The research examines how green accounting (GA) and Corporate Social Responsibility (CSR) affect Environmental Auditing Oversight (EAO) in manufacturing firms. It evaluates how transparent environmental cost reporting and CSR initiatives affect compliance with auditing standards. Research Methods This study relied on quantitative data analyzed using multiple linear regression with the Partial Least Squares (PLS) method, formulating and testing two hypotheses—(1) that Green Accounting (GA) through environmental costs has a significant impact on Environmental Auditing Oversight (EAO), and (2) that Corporate Social Responsibility (CSR) activities have a significant impact on EAO—which was operationalized as a binary variable based on ISO 14001 certification. Research Results and Findings. The study revealed that Green Accounting (GA) is a far stronger and more significant predictor of Environmental Auditing Oversight (EAO), thereby legitimizing and reinforcing stakeholder theories which posit that mandatory environmental cost disclosure for compliance enhances the level of auditing to a far greater extent than voluntary disclosure through Corporate Social Responsibility (CSR) initiatives.